“The people who are Illyrians and Celts”: Strabo and the identities of the ‘barbarians’ from Illyricum* - Dzino, Danijel (Arheološki vestnik, 2008)
This work re-examines the perception of the ancient geog-rapher Strabo in relation to the Iapodes as a ‘mixed people’, and places this in the context of current scholarly debates on the nature of the identity of pre-historic and proto-historical peoples of the Mediterranean ‘periphery’.